2012
DOI: 10.1016/j.micres.2012.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of phosphate solubilizing bacteria able to enhance the growth and aloin-A biosynthesis of Aloe barbadensis Miller

Abstract: The effect of four phosphate solubilizing bacteria (PSB) was studied on growth and aloin-A content of Aloe barbadensis in soil containing tricalcium phosphate (TCP). PSB were identified based on 16S rRNA gene sequencing as Pseudomonas synxantha, Burkholderia gladioli, Enterobacter hormaechei and Serratia marcescens. These PSB solubilized 25-340 μg ml(-1) of TCP into the liquid phase. The treatment of plants with individual PSB or mixture of these increased soil available P, P uptake in plants and plant growth.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
88
1
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(99 citation statements)
references
References 44 publications
6
88
1
4
Order By: Relevance
“…The soluble P content in soils and P uptake of plants should be detected furtherly to explain this phenomenon. Gupta et al (2012) found that the treatment of plants with individual PSB or mixture of them increased soil available P and P uptake in leaves of Aloe barbadensis, and consequently elevated all parameters of A. barbadensis, including leaf length, root length, total number of leaves, total gel volume, dry gel weight, and dry rind weight. However, some researchers had different results.…”
Section: Effects Of Psb On Plant Growthmentioning
confidence: 94%
See 1 more Smart Citation
“…The soluble P content in soils and P uptake of plants should be detected furtherly to explain this phenomenon. Gupta et al (2012) found that the treatment of plants with individual PSB or mixture of them increased soil available P and P uptake in leaves of Aloe barbadensis, and consequently elevated all parameters of A. barbadensis, including leaf length, root length, total number of leaves, total gel volume, dry gel weight, and dry rind weight. However, some researchers had different results.…”
Section: Effects Of Psb On Plant Growthmentioning
confidence: 94%
“…Phosphorus (P) is one of the major macronutrients important for the growth and development of plants, and it is involved in essential metabolic pathways, including photosynthesis, biological oxidation, nutrient uptake, and cell division (Illmer & Schinner, 1992;Gupta et al, 2012). A large portion of the total P in the soil is insoluble and unavailable for plant uptake.…”
Section: Introductionmentioning
confidence: 99%
“…Root length ranged from 6.03 cm to 10.78 cm; this variable increased 30.14% compared to the not inoculated control pitahaya seedlings (Figure 1). Gupta et al (2012) found the maximum increase in dry rind weight (51.8%) in plants treated with P. synxantha, whereas in case of root length, maximum stimulatory effect was seen in S. marcescens-treated plants.…”
Section: Resultsmentioning
confidence: 84%
“…A wide range of soil fungi are reported to solubilize insoluble phosphorous such as Aspergillus niger and Penicillium species, which are the most common fungi capable of phosphate solubilization (Whitelaw et al, 1999). Exploration of phosphate solubilizing microorganisms has been conducted by many researchers from soils (Chen et al, 2006;Widawati et al, 2008;Gupta et al, 2012), mangrove (Vazquez et al, 2000;Holguin et al, 2001), and rhizosphere (Chung et al, 2005;Poonguzhali et al, 2008;Oliveira et al, 2009 (Kumar et al, 2014). The principal mechanism for many soil fungi and bacteria can solubilize inorganic phosphate into soluble form through the process of acidification, chelation, exchange reactions and production of organic acids (Han, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The principal mechanism for many soil fungi and bacteria can solubilize inorganic phosphate into soluble form through the process of acidification, chelation, exchange reactions and production of organic acids (Han, 2006). Acid phosphatases play a major role in the mineralization of organic phosphorus in soil phosphate solubilization effect is mainly through the reaction between organic acids excreted from organic matters with phosphate binders such as Al, Fe, and Ca, or Mg to form stable organic chelates to free the bound phosphate ion (Arcand and Schneider, 2006;Gupta et al, 2012). Phosphorus deficiency is the most important problem of Ethiopian soil and more than 70 to 75% of highland soils are characterized by phosphorus deficiency (Beyene, 1982).…”
Section: Introductionmentioning
confidence: 99%